1994
DOI: 10.1007/bf01627913
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical basis of a fascio-cutaneous pedicle flap based on the infero-lateral collateral artery of the leg

Abstract: An anatomical study of 30 cases has been performed on the vascularisation of the distal third of the antero-lateral compartment of the leg, with particular reference to the relations of the infero-lateral collateral artery of the anterior tibial artery, the perforating branch of the peroneal artery, and the antero-lateral malleolar artery. A fascio-cutaneous pedicle flap based on the infero-lateral collateral artery is described noting that the superior, anterior, and posterior limits are similar to those of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 4 publications
3
7
1
Order By: Relevance
“…However, our study revealed in 80% of cases a distinct branch as well as several smaller branches. Our findings are consistent w i t h o t h e r i n v e s t i g a t i o n s who observed malleolar branches originating from the level of the ankle joint-line to about 5 cm proximal to it [6,11,12,17,19,34].…”
Section: Discussionsupporting
confidence: 91%
“…However, our study revealed in 80% of cases a distinct branch as well as several smaller branches. Our findings are consistent w i t h o t h e r i n v e s t i g a t i o n s who observed malleolar branches originating from the level of the ankle joint-line to about 5 cm proximal to it [6,11,12,17,19,34].…”
Section: Discussionsupporting
confidence: 91%
“…The potential problems of the flap [ 9 ] include some amount of venous congestion in reversed island flaps, painful neuroma as a result of a lesion of the superficial peroneal nerve, anatomic vascular variations [ 9 , [14] , [16] , [17] , [18] , [19] , [20] , [21] ], and the donor site concern, especially in young women. The usefulness of lateral supramalleolar flap has been demonstrated by its use as a delay flap [ 19 , 22 ] for tendon Achilles' coverage in difficult situations like Werner's syndrome, coverage of ischemic ulcer in Buerger's disease [ 20 ], as a free flap for oral coverage [ 14 ] and limb reconstruction [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Certain anatomic variations of the flap include the inconstant but frequent presence of a proximal inferolateral collateral artery [ 16 , 17 ], variations in the level of anastomosis between the perforating branch of the peroneal artery and the anterolateral malleolar artery arising from the anterior tibial artery, presence of the anterior peroneal artery, presence of a vascular network instead of a well-defined artery, absence of the perforating branch of the peroneal artery [ 16 , 17 ] and the basis of cutaneous circulation solely on anterior tibial perforators.…”
Section: Discussionmentioning
confidence: 99%
“…For patients who have cosmetic consideration, perforator-based adipofascial flap is also a good option with the use of ASMA. [ 20 21 22 23 24 ]…”
Section: Discussionmentioning
confidence: 99%